2016
DOI: 10.1177/2325957416680028
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Patients with Very-Low-Level HIV Viremia: A Community-Based Study

Abstract: Objective: Very-low-level viremia (VLLV) is a relatively new concept in the realm of human immunodeficiency virus (HIV) care. Newer generation assays are now able to detect plasma HIV RNA Viral Load (VL) levels as low as 20 copies/mL. The authors characterized patients with VLLV (VL between 20 and 50 copies/mL) in order to identify possible risk factors associated with virologic failure and poor clinical outcomes. Methods: The authors reviewed 119 consecutive charts of patients with VLLV. Sociodemographic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Past research has shown that patients with a slower time to achieving <50 copies/mL are more likely to continue treatment with residual viremia [13], and when <50 copies/mL occurs >6 months after initiating ART, they have an almost 2-fold risk of subsequent VR [6]. Reports with clearer evidence have stated that the inability to achieve UL-VL during firstline therapy could lead to a higher risk of VR in certain settings [33, 34], whereas others failed to observe similar results [35]. In our study, we observed that patients without VR were able to suppress UL-VL not detected at a significantly faster rate, similar to patients with “high” suppression of UL HIV-RNA during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that patients with a slower time to achieving <50 copies/mL are more likely to continue treatment with residual viremia [13], and when <50 copies/mL occurs >6 months after initiating ART, they have an almost 2-fold risk of subsequent VR [6]. Reports with clearer evidence have stated that the inability to achieve UL-VL during firstline therapy could lead to a higher risk of VR in certain settings [33, 34], whereas others failed to observe similar results [35]. In our study, we observed that patients without VR were able to suppress UL-VL not detected at a significantly faster rate, similar to patients with “high” suppression of UL HIV-RNA during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, ART delays the progression to cirrhosis in HIV/HCV co-infection[90,91]. Patients with undetectable or low levels of HIV RNA tend to develop liver disease gradually compared to patients with detectable viremia[92,93]. Furthermore, HIV treatment reduces the complications of the end-stage liver diseases, such as hepatocellular carcinoma (HCC) and death[94-96].…”
Section: Treatment Of Hiv/hcv and Hiv/hbv Co-infections With Art And Daamentioning
confidence: 99%
“…Los estudios publicados hasta el presente han demostrado hallazgos contradictorios en relación con la presencia de CVBG y el riesgo posterior de FV. Algunas publicaciones han observado que la presencia de CVBG es frecuente y que no se asocia con el desarrollo posterior de FV 5,9 . Otros estudios mostraron que los pacientes con CVBG tuvieron mayor riesgo de evolucionar a FV que los pacientes que se mantuvieron persistentemente indetectables 4,6,7 .…”
Section: Discussionunclassified
“…Los autores consideraron que los factores que contribuyeron a la presencia de CVBG intermitente o permanente podrían ser la existencia de reservorios virales, variaciones o error de laboratorio, continua replicación viral en tejidos y disminución de la adherencia. La CVBG por períodos prolongados podría estar asociada a activación inmune, aunque no se puede predecir el impacto clínico que conlleva 5 .…”
Section: Vih / Sidaunclassified